Theoretical investigation of dissociative electron attachment (DEA) study for halogen targets. Issue 17 (January 2020) - Vinodkumar, M; Yadav, H; Limbachiya, C; Vinodkumar, P C
Synopsis: Recently dissociative electron attachment (DEA) study has geared up due to its many fold applications in various fields. Here we have presented some of the results of DEA cross sections of few halogen targets of interest.